Pengaruh Beban Kerja dan Disiplin Kerja TerhadapKinerja pada Karyawan CV. Matahari Megah Mandiri Sukoharjo - Saila Al Fiqhiyyah, Taswa; Sutarno (Teewan Journal Solutions, 2025)
Employee performance is very important to pay attention to because performance is one of the determinants in achieving company performance in an effort to achieve company goals. The phenomenon of decreasing employee performance occurred at CV Matahari Megah Mandiri which was thought to be influenced by high workloads and poor work discipline. This research was conducted to analyze whether there is a significant influence of workload and work discipline on the performance of CV Matahari Megah Mandiri employees. The population in this study was all 33 employees of CV Matahari Megah Mandiri, so the sampling technique used was a saturated sample. The data analysis techniques used are validity test, reliability test, classical assumption test, multiple linear regression analysis, t test, F test and coefficient of determination test. The results of the validity test show that all the overall variable question items are declared valid after removing question items Y.2 and Y.7, the reliability test shows that the questionnaire items are reliable. The classical assumption test shows that all variables pass the test. Multiple linear regression analysis shows that all variables have a positive effect with the equation Y= 8.521 + 0.312X1 + 0.232X2 + e. The t test shows that workload does not have a significant effect on employee performance, while work discipline has a significant effect on employee performance at CV Matahari Megah Mandiri. The F test obtained that the research model used was correct, and the coefficient of determination test obtained that the workload and work discipline variables were able to explain the effect on employee performance of 33.5%.